IMPLEMENTATION OF CHRISTOLOGICAL UNDERSTANDING IN CHRISTIAN RELIGIOUS EDUCATION IN SCHOOLS IN THE INDUSTRY 4.0 ERA - Yupe Usiel; Vicky Paat; Sinaga, Maywan (Jurnal Matetes STT Ebenhaezer, 2023)
There is a lot of understanding or information about Christology in various literatures and social media at this time and it is easy to find it, therefore every believer should select the source so that it does not cause a misunderstanding and lead to the loss of the substance of Christology. It is undeniable that society in this modern era greatly influences the issues and development of Christological understanding. In this paper, we will discuss the implementation of Christology and Christian Religious Education Learning in schools in the Industrial 4.0 era. Learning Christian Religious Education in schools also has a very important role to build and maintain an understanding or information about true Christology based on the Bible, especially entering a new era that is quite significant in the development of information and communication technology. Referring to some of the statements above, we need to study the implementation of Christology in Christian Religious Education in schools in the industrial era 4.0 to further complement our understanding of the Lord Jesus Christ.